A COMPREHENSIVE REVIEW ON HYDROGELS - Nagam, Santhi Priya; Jyothi, A. Naga; Poojitha, J.; Aruna, Santhosh; Nadendla, Rama Rao (International Journal of Current Pharmaceutical Research, 2016)
Polymers play a vital role in pharmaceutical development. Efforts have been continuously made to search a polymer that act in a controlled& desired way. Hydrogel development has solved many such issues. Hydrogels are hydrophilic, three-dimensional networks. Which are able to imbibe large amounts of water or biological fluids & thus resembles to a large extent, a biological tissue. They are insoluble due to the presence of physical or chemical crosslinks such as entanglements& crystallites. These materials can be synthesized to respond to a number of physiological stimuli present in the body, such as PH, ionic strength, temperature. The main aim of this article is to give a concise review on introduction, preparation methods, types, & various applications of hydrogels in the pharmaceutical field.